Advanced polymeric coatings and their applications: green tribology (2019)
In this article, different advanced polymeric coatings and their applications are reviewed. Polymeric coatings have broad properties and functions; herein we discuss the coatings’ deposition methods and three different functional advanced polymeric coatings, namely, tribological coatings, superhydrophobic coatings and self-healing coatings. Advanced tribological polymeric coatings such as polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), and aromatic thermosetting copolyester (ATSP) exhibited excellent wear resistance and low friction, when sliding against different counter surfaces. Hydrophobic coatings prevent the coatings from water wetting by their surface structure and low surface energy, and self-healing coatings can recover or maintain their functionality after damage